Effect of allelic variation at the Glu-3/Gli-1 loci on breadmaking quality parameters in hexaploid wheat (Triticum aestivum L.). (March 2015) - Bonafede, Marcos D.; Tranquilli, Gabriela; Pflüger, Laura A.; Peña, Roberto J.; Dubcovsky, Jorge
Abstract: Low molecular weight glutenin subunits (LMW-GS) encoded by the Glu-3 loci are known to contribute to wheat breadmaking quality. However, the specific effect of individual Glu-3 alleles is not well understood due to their complex protein banding patterns in SDS-PAGE and tight linkage with gliadins at the Gli-1 locus. Using DNA markers and a backcross program, we developed a set of nine near isogenic lines (NILs) including different Glu-A3/Gli-A1 or Glu-B3/Gli-B1 alleles in the genetic background of the Argentine variety ProINTA Imperial. The nine NILs and the control were evaluated in three different field trials in Argentina. Significant genotype-by-environment interactions were detected for most quality parameters indicating that the effects of the Glu-3/Gli-1 alleles are modulated by environmental differences. None of the NILs showed differences in total flour protein content, but relative changes in the abundance of particular classes of proteins cannot be ruled out. On average, the Glu-A3f, Glu-B3b, Glu-B3g and Glu-B3i Man alleles were associated with the highest values in gluten strength-related parameters, while Glu-A3e, Glu-B3a and Glu-B3i Chu were consistently associated with weak gluten and low quality values. The value of different Glu-3/Gli-1 allele combinations to improve breadmaking quality is discussed.